Pembentukan dan Pembinaan Kelompok Tani Kelinci dalam Rangka Pengembangan Desa Wisata di Soropati, Hargotirto, Kokap, Kulon Progo - Naela Wanda Yusria Dalimunthe; Clara Ajeng Artdita; Fajar Budi Lestari (Pengabdian dan Pengembangan Masyarakat Sekolah Vokasi UGM, 2019)
Community Service Activities in 2018 have been implemented in Soropati Village, Hargotirto, Kokap, Kulon Progo. The purpose of this activity was to provide information on the maintenance and formation of rabbit farmer groups by involving the academics of the Diploma in Animal Health Program, Department of Biological and Veterinary Technology, Vocational School, Gadjah Mada University with Animal Health Centre in Kokap so that a better communication between academics, officers, and breeders community should be conducted well. The activity is carried out by providing information and training transfers regarding the management of rabbit maintenance including rabbit species, housing management, feed, and breeding. The implementation of this program was carried out by giving professional speech and interactive discussions then comparative studies to rabbit farmers who had been successful, counseling and fostering. The result of this activity is that the Mantep Makaryo farmer group has been formed which is engaged in the maintenance and cultivation of rabbits. Development of sustainable breeders needs to be carried out to improve health management and the development of rabbit farms.